2016
DOI: 10.3109/15569527.2016.1169541
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological aspects of synthetic cannabinoid addiction

Abstract: Given the increased prevalence of SC use in our country and around the world, dermatologists should continue to familiarize themselves with the common mucocutaneous markers of this substance use. Awareness of signs of SCs use will facilitate earlier diagnose, intervention, and directed treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…Here, it is involved in a large number of biological processes, such as proliferation, growth, differentiation and survival, immunocompetence, tolerance 26 and melanogenesis 27 . It was recently shown that abuse of synthetic cannabinoids can result in dermatologic disorders, such as premature skin ageing, hair loss and greying, or acne 28 , indicating that cannabinoid signalling can influence skin biology.…”
mentioning
confidence: 99%
“…Here, it is involved in a large number of biological processes, such as proliferation, growth, differentiation and survival, immunocompetence, tolerance 26 and melanogenesis 27 . It was recently shown that abuse of synthetic cannabinoids can result in dermatologic disorders, such as premature skin ageing, hair loss and greying, or acne 28 , indicating that cannabinoid signalling can influence skin biology.…”
mentioning
confidence: 99%
“…The clinical observation that cannabinoid abuse can be accompanied by acne, already highlights how cannabinoid signaling may influence human sebocyte biology [88]. Indeed, expression of CB 1 (in the differentiated, central cells) and CB 2 (predominantly in the basal, non-differentiated sebocytes) receptors in human SGs was first demonstrated by Ständer and her co-workers in 2005 [111].…”
Section: Translational Potential Of the Cutaneous Cannabinoid Signmentioning
confidence: 99%
“…Similar to SGs, the biology of HFs is also influenced by cannabinoids. Indeed, as mentioned above, abuse of certain synthetic cannabinoids was shown to result in hair loss and graying [88], and it is well-proven that CB 1 is expressed in human HFs, whereas regarding the expression of CB 2 contradictory findings have been published so far [111,130,131,132,133]. Of great importance, prototypic eCBs (i.e., AEA and 2-AG) were shown to be produced in human HFs, among which 30 μM AEA (but not 2-AG) was proven to inhibit hair growth by inducing premature catagen entry in a CB 1 -dependent manner, but, somewhat surprisingly, it did not influence the pigmentation of HFs.…”
Section: Translational Potential Of the Cutaneous Cannabinoid Signmentioning
confidence: 99%
See 2 more Smart Citations